2016
DOI: 10.2527/jas.2015-9427
|View full text |Cite
|
Sign up to set email alerts
|

Group and individual sow behavior is altered in early gestation by space allowance in the days immediately following grouping1

Abstract: Aggression between domestic sows is greatest when sows are first introduced to each other and hierarchies form. The aim of this study was to determine the effect of a spacious "mixing pen" on sow aggression and stress. Sows were mixed into groups of 6 and allowed 2 (LOW; 8 groups and 48 sows), 4 (MED; 7 groups and 42 sows), or 6 m/sow (HIGH; 7 groups and 42 sows) for 4 d after mixing, at which point all pens were equalized to 2 m/sow. Salivary cortisol concentration and injury counts were measured on d -1, 0, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 20 publications
2
16
0
Order By: Relevance
“…As discussed previously, the sows in this piggery are accustomed to group housing and hierarchy formation, therefore may adjust more readily to group-housed situations [39], resulting in the saliva cortisol concentrations not being affected by mixing. The cortisol levels in this experiment are comparable to levels reported by Greenwood et al (2016), in the same piggery with similar genetics [31]. The overall effect of diet on aggression was limited.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…As discussed previously, the sows in this piggery are accustomed to group housing and hierarchy formation, therefore may adjust more readily to group-housed situations [39], resulting in the saliva cortisol concentrations not being affected by mixing. The cortisol levels in this experiment are comparable to levels reported by Greenwood et al (2016), in the same piggery with similar genetics [31]. The overall effect of diet on aggression was limited.…”
Section: Discussionsupporting
confidence: 86%
“…Also, the non-aggression-based behaviors in this study showed that sows spent more time active and exploring, and therefore less time resting, in the early days after mixing, compared with day six post-mixing. Previous research on the same population found a similar reduction in aggression within 24 h [31], and a study by Moore et al (1993) saw a reduction in aggression as soon as 1 h following mixing [37]. Additionally, Hemsworth et al (2013) found that mixing stress in sows was most obvious soon after mixing, subsiding by days 8 and 9 [39].…”
Section: Discussionmentioning
confidence: 70%
“…A modification of the assessment described by Karlen et al (2007) was used to describe lesion counts in all treatments [2]. Each side of the sow’s body was divided into 21 areas and the number of skin lesions in each area was counted [27,28]. Sows were also placed into an injury score group and given a rank from 0–5 based on the number of injuries; sows with 0–10 injuries were group 0; 11–20 were group 1; 21–30 were group 2; 31–40 were group 3; 41–50 were group 4; 50+ were group 5.…”
Section: Methodsmentioning
confidence: 99%
“…Saliva samples were collected 1 hr before and after each feeding time and 3 hr after the last feeding occasion (i.e., 0630, 0830, 1030, 1230, 1430, 1630, and 1830 hours) using neutral synthetic swab Salivette (Sarstedt, Aktiengesellshaft and Co, Numbrecht, Germany) attached to cotton string. The string was hung in the stall to allow sows to chew on the Salivette until it became completely soaked with saliva ( Greenwood et al, 2016 ). Saliva samples were collected on ice and centrifuged 2 hr later at 2,500 × g for 10 min at 4 °C.…”
Section: Methodsmentioning
confidence: 99%